2008
DOI: 10.4049/jimmunol.181.1.546
|View full text |Cite
|
Sign up to set email alerts
|

Differential CMV-Specific CD8+ Effector T Cell Responses in the Lung Allograft Predominate over the Blood during Human Primary Infection

Abstract: Acquisition of T cell responses during primary CMV infection in lung transplant recipients (LTRs) appear critical for host defense and allograft durability, with increased mortality in donor+/recipient− (D+R−) individuals. In 15 D+R− LTRs studied, acute primary CMV infection was characterized by viremia in the presence or absence of pneumonitis, with viral loads higher in the lung airways/allograft compared with the blood. A striking influx of CD8+ T cells into the lung airways/allograft was observed, with inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
30
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 58 publications
4
30
0
Order By: Relevance
“…Thus, it is concluded that the effects of CY therapy in MCMV-infected mice extend beyond early increased viral replication from transient immunosuppression. These observations are also consistent with human models of primary CMV infection, such as our studies in lung transplant where it was demonstrated that the magnitude of expansion of CMV-specific T cells in the lung does not necessarily correlate with BAL viral load levels (32).…”
Section: Discussionsupporting
confidence: 89%
“…Thus, it is concluded that the effects of CY therapy in MCMV-infected mice extend beyond early increased viral replication from transient immunosuppression. These observations are also consistent with human models of primary CMV infection, such as our studies in lung transplant where it was demonstrated that the magnitude of expansion of CMV-specific T cells in the lung does not necessarily correlate with BAL viral load levels (32).…”
Section: Discussionsupporting
confidence: 89%
“…Therefore, a deeper understanding is required of how the level of HCMV replication is affected by the immune system, in particular by cytotoxic CD8+ T cells, which are essential for containing HCMV (14)(15)(16)(17)(18)(19)(20)(21)(22)(23).…”
Section: Discussionmentioning
confidence: 99%
“…From these 67 patients, 1121 plasma samples with a mean of 17 samples per patient (range: 8-43) were collected during the follow-up at a mean interval of 25.6 days (range: 2-95), and HCMV DNA loads were measured. In parallel, a total of 758 heparinized whole-blood samples with a mean of 11.5 serial samples per patient (range: [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] were acquired prospectively at a mean interval of 31.7 days (range: 4-111) and were tested for HCMV-specific CD8+ T cell responses using the QuantiFERON R -CMV assay (Cellestis GmbH, a QIAGEN company). Of these, 598 samples (78.9%) gave a determinate result.…”
Section: Prospective Recruitment Of Patients and Acquisition Of Seriamentioning
confidence: 99%
See 1 more Smart Citation
“…1 in viral infections (21), especially for prevention and control of primary CMV disease after transplantation (7,22,23). However, other transplantation studies have also indicated an important role for CD4 1 T cells in CMV viral control after transplantation (24)(25)(26)(27)(28).…”
Section: Discussionmentioning
confidence: 99%